High performance microwave absorption through multi-scale metacomposite by intergrating Ni@C nanocapsules with millimetric polystyrene sphere. (7th August 2018) - Liu, R G; Li, Y X; Li, C H; Wang, J Y; Wang, Z H; Zhang, Y H; Qi, F; Zhang, X F
Abstract: We demonstrated the desirable microwave absorption properties in a 3D Ni@C/polystyrene (PS) sphere metacomposite, originated from the electromagnetic transform between the permittivity and the permeability. The metacomposite is composed of an array of millimetric PS spheres coated by high-performance Ni@C nanocapsule microwave absorbents. Such a phenomenon is caused by the near-field electromagnetic interaction, modeled by a theoretical simulation, resulting in the reciprocal resonances for the dielectric and magnetic loss factors. The resonance frequencies are proportional to the PS sphere size. This study provides a bottom-up strategy to fabricate the metacomposite and meanwhile has important implications in understanding the electromagnetic transformation.